KESIAPAN MADRASAH IBTIDAIYAH DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA - SEKARINASIH, ANGGITIYAS (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
This research aims to describe how prepared Madrasah Ibtidaiyah is in implementing the Merdeka curriculum. This descriptive-analytic research was conducted at MI Ma'arif NU Banjarparakan Rowalo and MI Ma'arif NU Beji in Banyumas Regency. The readiness of madrasah ibtidaiyah in implementing the Merdeka curriculum is seen in three aspects, namely in terms of human resources, facilities and infrastructure, and the programs carried out. The research results show that: 1) in terms of human resources, both MIs have minimal readiness; 2) in terms of facilities and infrastructure, both MIs are equally limited in terms of the books used by students. Meanwhile, basic infrastructure such as classrooms and in-focus is more complete at MI Ma'arif NU Beji; 3) preparations from the program aspects of MI Ma'arif NU Beji and MI Ma'arif NU Banjarparakan have made maximum efforts to prepare themselves for the implementation of the Merdeka curriculum; 4) The preparations at MI Ma'arif NU Beji and MI Ma'arif NU Banjarparakan have at least given an initial idea or begun to recognize key terms in the Merdeka curriculum. Keywords: Madrasah Readiness, Implementation, Independent Curriculum